Analisis Anggaran Biaya Produksi Crude Palm Oil (CPO) Dengan Metode ABC (Activity Based Costing) Pada CV. Hamparan Sawit Makmur - Abdillah, Muhammad Mar'ie; Sutrisno, Sutrisno; Prasetyo, Healthy Aldriany (Universitas Medan Area, 2024)
CV. Hamparan Sawit Makmur is a company engaged in the palm oil processing business which produces crude palm oil and kernels. The conditions that occur in the company show that in implementing the company's production cost budget, there are still detrimental deviations between the budget and the actual production costs. This research aims to determine the factors that cause high deviations between production cost budgets and cost realization, and analyze the influence of production cost budgets on effectiveness in controlling production costs and determining more accurate cost of production using the Activity Based Costing method ( A B C). It is hoped that this research can provide input for company management regarding the role of the budget as a tool for monitoring the company's operational performance as well as the role of the cost of production on company profits. From the results of the research carried out, the calculation of the cost of production using the ABC method is more accurate than the traditional method used by the company, using the ABC method the value obtained is IDR 4,696.5/Kg, while the traditional method used by the company is IDR 6,226. 04,-/Kg. So the difference value obtained is Rp. 1,529.54,-/Kg.